An institutional perspective on the social outcome of entrepreneurship: Commercial microfinance and inclusive markets - Ault, Joshua K (Journal of International Business Studies, 2016)
This study applies an institutional perspective to a current debate in social entrepreneurship about the relative effectiveness of commercial vs non-profit methods of building inclusive markets for the poor. While some observers argue that for-profit ventures are needed to serve the poor on a large scale, others express concern that commercialization causes mission drift, a phenomenon where ventures migrate to wealthier clients over time. A multilevel analysis of 2679 for-profit and non-profit microfinance lenders in 123 countries over 15 years supported the hypotheses that commercialization contributes to mission drift away from market inclusivity, but that national levels of “state fragility” moderate this effect. In countries with a low level of state fragility, it was less costly to serve the poor, which decreased pressure on commercial actors to shift to wealthier clients to achieve profitability. An important implication of this finding is that institutions influence not only the number of entrepreneurs found in a particular location but also the social impact of entrepreneurial strategies and actions.